Foxp3+ regulatory T cell therapy for tolerance in autoimmunity and solid organ transplantation - Sanders, Jes M.; Jeyamogan, Shareni; Mathew, James M.; Leventhal, Joseph R. (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) are critical for tolerance in humans. The exact mechanisms by which the loss of peripheral tolerance leads to the development of autoimmunity and the specific role Tregs play in allograft tolerance are not fully understood; however, this population of T cells presents a unique opportunity in the development of targeted therapeutics. In this review, we discuss the potential roles of Foxp3+ Tregs in the development of tolerance in transplantation and autoimmunity, and the available data regarding their use as a treatment modality.